2017
DOI: 10.1108/jcom-04-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

How symmetrical employee communication leads to employee engagement and positive employee communication behaviors

Abstract: Purpose The purpose of this paper is to examine how a company’s symmetrical internal communication efforts could influence its employees’ perception of relationship outcomes with the company and the subsequent employee communication behaviors about the company to others and their turnover intention. Additionally, the mediation effects of employee-organization relationship (EOR) quality between symmetrical internal communication and employee engagement were tested. Design/methodology/approach The study collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
257
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(288 citation statements)
references
References 64 publications
21
257
2
8
Order By: Relevance
“…In line with this, strategic communication researchers have started to pay attention to the importance of employees for the external and internal communication of organizations. Although employees' importance for the communication of organizations has been acknowledged by strategic communication and public relations research for almost three decades (e.g., Grunig, 1992), and several researchers label employees as "strategic constituents" (Kang & Sung, 2017;Kim & Rhee, 2011), most researchers agree that employees traditionally have been viewed as passive recipients of communication activities rather than strategic communicators whose communication activities have…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, strategic communication researchers have started to pay attention to the importance of employees for the external and internal communication of organizations. Although employees' importance for the communication of organizations has been acknowledged by strategic communication and public relations research for almost three decades (e.g., Grunig, 1992), and several researchers label employees as "strategic constituents" (Kang & Sung, 2017;Kim & Rhee, 2011), most researchers agree that employees traditionally have been viewed as passive recipients of communication activities rather than strategic communicators whose communication activities have…”
Section: Introductionmentioning
confidence: 99%
“…For example, Salanova et al (2005) conducted a study on 114 service organizations in Spain and found that service employees' engagement can create a favorable service climate, that in turn, enhance the employees' performance. Recently, Kang and Sung (2017) found that internal communication process can enhance the level of employee engagement that ultimately lead to increase employee performance by using a sample of 438 service sector employees in South Korea. With these research findings, scholars have identified the essence of giving priority to enhance the employee engagement (Bakker, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that employees are aware of their situation, but there are barriers in communication, or they lack the power to change their circumstances. Timmins (2011) and Kang and Sung (2017) argue that effective communication is at the forefront of successful relationships in an organisation, where trust, transparency and appropriate behaviours that unite employees. According to Zheng, Molineux, Mirshekary and Scarparo (2015) good communication is closely linked with employee welfare as employees are likely to approach their colleagues or leaders with ideas or concerns.…”
Section: Communication and Leadershipmentioning
confidence: 99%
“…As described by Kang and Sung (2017), and Kemerer and Cwiekala-Lewis (2017), leaders are responsible for ensuring clear lines of communication throughout an organisation, and the resources to manage emotional stress and fatigue as captured in this interviewee's comment:…”
Section: Communication and Leadershipmentioning
confidence: 99%